THE IMPLEMENTATION OF FLIPPED CLASSROOM THROUGH THEMATIC LEARNING MODEL AT SD NEGERI BATULACCU MAKASSAR - Abner Buttu Sarira; Asdar Asdar; Sundari Hamid (Teaching English as a Foreign Language Overseas Journal, 2022)
The Effectiveness of the Application of the Flipped Classroom Model in Class V Thematic Learning at SD Negeri Batulaccu Makassar. Skripsi of Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, University of Bosowa. This study aims to determine the effectiveness of the application of the flipped classroom model in the fifth-grade thematic learning at SD Negeri Batulaccu Makassar. The type of research used in this study is a quantitative experimental design with a one-group pretest-posttest design. The research sample is class V students, totaling 29 students. The results of the t-test study obtained the results of t Calculate t Table obtained the results of 11.341 2.052 then H0 is rejected and Ha is accepted. Thus, it can be concluded that the flipped classroom model is effectively applied to the thematic learning of class V at SD Negeri Batulaccu Makassar.